2006
DOI: 10.1159/000097535
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Aging Is Associated with Unaltered Production of Immunoreactive Growth Hormone but Impaired Neuroimmunomodulation

Abstract: Background: Both endocrine and immune systems are continuously remodeled during aging. Objective: Here, we investigated to what extent adrenal and somatosenescence are associated reciprocal changes in the immune system during strictly healthy aging. Methods: Forty-six elderly subjects and 33 young adults were recruited according to the health criteria of the SENIEUR protocol. Peripheral blood mononuclear cells were isolated and stimulated in vitro with lipopolysaccharide or phytohemagglutinin to assess the pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
2

Year Published

2008
2008
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 102 publications
(63 reference statements)
2
25
2
Order By: Relevance
“…All subjects were screened according to the strictly healthy criteria established by the SENIEUR protocol [16] . The health conditions were checked according to previous work [12,13] and were based on accurate clinical investigations and hematological and biochemical parameters. Forty-one (32 females) strictly healthy and primary caregivers (mean 8 SD age: 60.56 8 11.56 years) and 33 strictly healthy (26 females) and non-stressed controls (mean 8 SD age: 60.27 8 14.10 years) were included in the study.…”
Section: Subjectsmentioning
confidence: 99%
See 1 more Smart Citation
“…All subjects were screened according to the strictly healthy criteria established by the SENIEUR protocol [16] . The health conditions were checked according to previous work [12,13] and were based on accurate clinical investigations and hematological and biochemical parameters. Forty-one (32 females) strictly healthy and primary caregivers (mean 8 SD age: 60.56 8 11.56 years) and 33 strictly healthy (26 females) and non-stressed controls (mean 8 SD age: 60.27 8 14.10 years) were included in the study.…”
Section: Subjectsmentioning
confidence: 99%
“…Healthy aging has been associated with neuroendocrine and immunological changes including hypothalamic-pituitary-adrenal (HPA) axis activation with increasing cortisol [12] and blunted cell-mediated immunity [13] . The caregivers of demented patients had further reduced T cell function as well as impaired steroid immunoregulation in association with increased cortisol levels compared to nonstressed elderly controls [2,14] .…”
Section: Introductionmentioning
confidence: 99%
“…In addition, it was observed that healthy elders had lower dehydroepiandrosterone (DHEA) levels (-54%) throughout the day compared to young adults [31] . Furthermore, elders also displayed a flat circadian pattern for DHEA secretion.…”
Section: Healthy Aging Is Associated With Emotional Distress and Incrmentioning
confidence: 99%
“…Indeed, we have observed that healthy SENIEUR elders were significantly more distressed, had activated HPA axis and significantly lower (-53.6%) T cell proliferation compared to young adults ( fig. 2 ) [31] . Interestingly, the HPA axis may be implicated with this change, since salivary cortisol levels were found negatively correlated to T cell proliferation.…”
Section: Similarities Between Aging and Chronic Gc Exposurementioning
confidence: 99%
See 1 more Smart Citation